Evaluating Adam Smith creating the wealth of nations - Henderson, Willie 1947- (Routledge, 2006)
This important new book builds on the understanding that Adam Smith's Wealth of Nations is best viewed as a cultural document, created within the context of eighteenth century notions of human nature, economy and argument, and that familiarity and rhetoric played a part in its success. Using discourse analysis, Henderson explores Smiths rhetorical strategies, relationships with his sources and readers, and his way of constructing his economic vision in writing. He expertly demonstrates techniques of text analysis to the reader in ways that promote a critical reading of Smith and which the reader can then transfer to the analysis of other texts relevant to the intellectual history of economics. Of great interest to those in the fields of economics and Marxism, Henderson's book evaluates the Wealth of Nations as a text of historical and modern-day significance.
Includes bibliographical references and index
Keywords: Smith, Adam -- 1723-1790 -- Inquiry into the nature and causes of the wealth of nations; Smith, Adam -- 1723-1790 -- Criticism and interpretation; Smith, Adam -- 1723-1790 -- Criticism, Textual; Smith, Adam <1723-1790> -- Inquiry into the nature and causes of the wealth of nations; Smith, Adam -- 1723-1790 -- An inquiry into the nature and causes of the wealth of nations; Kommentar